EVOLUTION OF THE FORMATION OF DISTANCE LEARNING IN UKRAINE AND THE MODERN WORLD - Ponomarova, Halyna; Kharkivska, Alla (My University, 2021)
The current stage of development of Ukraine is focused on the accelerated advancement of the state into the community of the 50 most competitive countries in the world. Due to this, the policy in the field of education is aimed at the formation of a national model of education, integrated into the global educational space and providing training for specialists who are competitive in the world labor market
Ponomarova H. Evolution of the formation of distance learning in Ukraine and the modern world / H. Ponomarova , А. Kharkivska // Laplage em Revista (International), Sept. - Dec. 2021. – Vol.7. – № 3. – Р. 353–362.
Keywords: дистанційне навчання, світовий ринок праці, конкурентність; distance learning, world labor market, competition; дистанционное обучение, мировой рынок труда, конкуренция